ANALISIS POTENSI RETRIBUSI PASAR KEBONPOLO, EFEKTIVITAS DAN KONTRIBUSINYA TERHADAP PAD KOTA MAGELANG TAHUN 2014-2018 - Indah Sekar Wangi; Rian Destiningsih (Jurnal Ekonomi-Qu, 2020)
This study aims to determine the level of contribution from the Kebonpolo Market levies and the effectiveness of fees to increase PAD in the City of Magelang. This study uses secondary data, the data used are the realization of PAD Magelang 2014-2018 data reports, Kebonpolo Market realization report data in Magelang City by using descriptive statistical methods and data on contribution and effectiveness reports in Magelang Pasar Kota 2014-2018. This research uses descriptive data analysis method. The results of this study indicate the level of contribution from the Kebonpolo Market service levies to the PAD of Magelang City is very poor and has decreased its contribution in 2016-2018, and the effectiveness of the Kebonpolo Market service fees towards the local government budget target. Magelang City Retribution is a very effective indicator or decreases in 2014-2016, and 2016-2017 increases while 2017-2018 decreases.